FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MEDICATION ERROR FASE DISPENSING DI INSTALASI FARMASI RS - yenny hartono; Sakundarno Adi; Chriswardani Suryawati (Dian Nuswantoro Semarang, 2020)
Medication errors can have an impact on patient safety which can result in disability and in the worse risk is the patient dies. The most frequent medication error is dispensing medication error. The objective of this research is to know the factors related to dispensing medication errors and how to prevent it. This was an observational study, a cross sectional design, study samples were 85 pharmacist and pharmacist assistant, data collected by questionnaire. Univariate, and multivariate analysis were applied in the data analysis. There is correlation between variables of gender (p = 0.025), marital status(p = 0.020) and employment status (0.021) with dispensing medication error. From multivariate analysis, the result show that there is relation between level of education (p = 0.000), employment status (p = 0.035) and workload (p = 0.006) with dispensing medication error. The occurance of medication error was lower on employee with higher education, and higher on employee that married and high work load. From this result, the hospital management need to do workload analysis and review the workload of pharmacist and pharmacist assistant to prevent dispensing medication error.